Publisher embargoes and institutional repositories: a case study of journal articles subject to an Australian funder mandate - Kirkman, Noreen; Haddow, Gaby (Information Research, 2021)
Introduction. Despite funder policies recognising the repository route as critical to achieving open access compliance, most accepted manuscripts in repositories have embargoes on access. This paper explored the extent to which embargoes hinder open access for grant recipients.